PREGABALIN DETERMINATION IN POSTMORTEM SAMPLES AND TOXICOLOGICAL SIGNIFICANCE IN FORENSIC CASES - Vujovic, Maja; Kostic, Emilija; Pančić, Dimitrije; Milosavljevic, Biljana; Stojanovic, Ivan; Karadzic, Radovan; Ilic, Goran (Acta medicae Medianae, 2021)
Pregabalin (PGB) was initially developed for the treatment of epilepsy, but nowadays it is used in the management of neuropathic pain, generalized anxiety disorder, and fibromyalgia. Over the past 10 years, PGB  from a prescription drug became a recreational drug. PGB was classified as having considerable “abuse liability.” Intoxications with PGB at the Institute of Forensic Medicine in Niš (South-east Serbia) in clinical and postmortem samples were noticed in recent years. The primary data consisted of the toxicological results analysis of postmortem blood and urine obtained in the authors’ laboratory during 2019. Cases of intoxications with a combination of PGB (concentrations above the therapeutic range) and other drugs and alcohol were included in this paper. Blood and urine samples were extracted using solid-phase extraction on Plexa, PCX, Agilent cartridges. Analysis method for pregabalin determination is gas chromatography with a mass spectrometer, while liquid chromatography with tandem mass spectrometry (Shimadzu), high-performance liquid chromatography with a photodiode array detector (Waters Alliance) and head-space gas chromatography with flame ionisation detector (Shimadzu) were used for other substances analysis. The abuse potential of PGB has created concerns about risks of respiratory depression and death when used with opioids or other central nervous system depressants, such as drugs found in our investigated cases. Autopsy results have shown deaths were violent and the main cause of deaths were overdose and additive, depressive effects of drugs and alcohol on CNS. Health professionals must be aware of this misuse potential, which could lead to abuse and dependence.
Keywords: pregabalin; postmortem samples; abuse; toxicology